No “Back Alley Clique”: The campaign to desegregate Chatham’s public schools, 1891-1893 - Shadd, Adrienne (Ontario History, 2007)
In 1891, the Kent County Civil Rights League was formed to seek redress in several areas in which the Black community of Chatham felt they were being wronged. The first issue they decided to tackle was the segregated school system. This paper looks at the events and personalities involved in this landmark action which has essentially gone unrecorded and unrecognized in Black Canadian historiography, but which resulted in the opening of all schools to Black children in that town.